Serum iron and serum ferritin levels in cholelithiasis: a randomized study - Arora, Bhavinder Kumar; Yadav, Anuj Kumar (International Surgery Journal, 2018)
Background: The role of iron in the pathogenesis of gallstone disease has not been well established so far. Iron deficiency has been shown to alter the activity of several hepatic enzymes, leading to increased cholesterol saturation of bile in gall bladder and hence promoting cholesterol crystallization.Serum iron, total iron binding capacity and transferrin saturation are not good indicators of iron status in individuals. In infection free situation, serum ferritin is an ideal indicator for diagnosis of iron deficiency. Methods: The study was conducted as a prospective study in the department of Surgery. The study population was divided into two groups; Case group with 200 patients with gallstone disease and control group with 50 patients without gallstone disease. Serum iron and ferritin contents of both groups will be analyzed and compared with each other. Results: In this study the gallstones are more prevalent in female population than males in ratio of 5.4:1. Serum iron in males was low in 41.93% not comparable 20.8% of control suggesting that low serum iron is not associated with Cholelithiasis in male. In males, serum ferritin was low in 64.5% of cases and 16.66% of controls. Serum ferritin levels were normal in 35.50% of cases and 66.66% of controls and above normal in 16.66% of controls suggesting that low serum ferritin is associated with gall stones in males. In this study, low serum iron was seen in 23.07% of females comparable to 23% low serum iron in control females and low ferritin was seen in 35.50% of female cases as compare to 15.38% of controls. Conclusions: It was concluded that a low body store of serum iron is a risk factor for cholelithiasis in females and serum iron, serum ferritin may be used as marker of iron store so that low serum iron status could be diagnosed at early stage.